2014
DOI: 10.1111/cod.12249
|View full text |Cite
|
Sign up to set email alerts
|

The dramatic increase in the rate of methylisothiazolinone contact allergy in Belgium: a multicentre study

Abstract: A dramatic increase in the rate of contact allergy caused by MI in cosmetics is occurring in Belgium. Notwithstanding the recent recommendation to discontinue the use of MI in leave-on cosmetics, safer use concentrations should also be determined for rinse-off products. Close monitoring of MI sensitization in the near future will be necessary, and the highest test concentrations reported for MI and MCI/MI should be included in the baseline series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
127
4
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(159 citation statements)
references
References 39 publications
(51 reference statements)
23
127
4
5
Order By: Relevance
“…Only in a very few cases was the product found to be not in compliance with the legislation. In some cases, the companies have taken voluntary measures to substitute a substance, e.g., such as the preservative MI with a known high sensitisation prevalence [11,12] with substances with a lower sensitising potential.…”
Section: Discussionmentioning
confidence: 99%
“…Only in a very few cases was the product found to be not in compliance with the legislation. In some cases, the companies have taken voluntary measures to substitute a substance, e.g., such as the preservative MI with a known high sensitisation prevalence [11,12] with substances with a lower sensitising potential.…”
Section: Discussionmentioning
confidence: 99%
“…This has clearly been exemplified by the introduction of MI into the European cosmetic market in 2005 where MI was given a positive opinion by the SCCS and entered onto Annex V as a preservative allowed for use in cosmetic products. The rapid increase of MI contact allergy has greatly contributed to the overall burden of contact allergy to preservatives, and thousands of European citizens most likely experience allergic contact dermatitis when being in skin contact with cosmetic products preserved with MI or when being exposed to evaporated MI from newly painted rooms [17][18][19].…”
Section: Temporal Trend Of Contact Allergy To Preservativesmentioning
confidence: 99%
“…Several retrospective observational studies from European countries have shown increasing prevalence rates of MI contact allergy from 1.5%-2.5% in 2010 to 6%-12% in 2014 in European contact dermatitis patients [7,17,[35][36][37][41][42][43]. No decline has yet been observed in surveillance data of European patients with contact dermatitis, and the relevance of the MI contact allergy exceeds 70%-80% [7].…”
Section: Contact Allergy To Methylisothiazolinonementioning
confidence: 99%
See 1 more Smart Citation
“…Methylisothiazolinone (MI) is frequently used in personal care products marketed for children, such as wet wipes, moisturizers, and body washes; this increased lately to epidemic proportions due to the massive increase in the use of cosmetic and other exposures [35]. Furthermore, oat and wheat have been described as contact allergens in personal care products, which can lead to protein contact dermatitis [36].…”
Section: Clinical Pictures and Patch Testing In Ad Childrenmentioning
confidence: 99%